Amblyomma cajennense (Fabricius, 1787) (Ixodida: Ixodidae): human parasitism and the first record from the Acre State, Western Brazilian Amazon - Souza, Vanessa L. de; Lima, Marcos S. de; Martins, Thiago F.; Costa, Franscio E. da; Silva, José R. O. da; Souza, José R. L. de (Entomological Communications, 2022)
The Cayenne tick, Amblyomma cajennense (Fabricius, 1787) (Ixodida: Ixodidae), parasitizes a range of vertebrate hosts, including humans, accidentally. Infestation by this species has important implications for public health, given that these ticks habitually bite humans and may act as the vectors of several pathogens. Here, we present a detailed case of human parasitism by A. cajennense and provide the first record of the occurrence of the species in the state of Acre, Brazil.